Method for determining amylose content of fresh rice sample - ZHONG Lian-jin; CHENG Fang-min (浙江大学学报. 农业与生命科学版, 2002)
Based on the effects of pH and sample concentration on determination of amylose content of rice sample, a new method for the determination was developed. A multivariate regression equation was formulated which reflects the relation of amylose content to starch concentration and absorbance at 620 nm of rice sample and permits the amylose content of rice sample to be calculated from the data of absorbance. Using this method, the interference from amylopectin during determination was eliminated and both amylose content and amylopectin content of rice sample could be obtained. Amylose content in the range of 5-50 mg/L could be determined with a relative deviation of less than 3 per cent and the C. V. was below 2.5 per cent. The far less amount of rice sample needed than that used in the classical method as suggested by Juliano in 1971 and simplicity in performance were the other advantages of the method. The method can be particularly adapted to determine the amylose content of fresh rice sample where the quantity available is limited.